Manufacturing process of handicraft imitating cast iron corrosion rust effect

By electrostatically adsorbing iron powder on the silicone mold and combining the cross-linking and curing treatment of unsaturated polyester resin and stone powder, the problems of high pollution and modeling restrictions of existing cast iron processes are solved, and the shape diversification and resistance of imitation cast iron crafts are achieved. Corrosion effect.

CN119388645APending Publication Date: 2025-02-07QUANZHOU NANYANG ARTS & CRAFTS IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411494454.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing cast iron corrosion effect product processes are high pollution and high energy consumption, and the molds limit the shape diversity of handicrafts, making it difficult to achieve corrosion resistance and body diversification effects.

Method used

The electrostatic adsorption effect of silicone mold and iron powder is adopted, combined with the mixture of unsaturated polyester resin and stone powder and color paste, and the cast iron effect is achieved through cross-linking and curing and oxidation treatment, and the anti-prevention is improved through brine oxidation and transparent paint hooding treatment. Corrosive.

Benefits of technology

It has achieved diversified shapes of handicrafts, and has good corrosion resistance, reducing production energy consumption and pollution.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of cast iron imitating material processing, and particularly discloses a manufacturing process of a cast iron corrosion rust effect imitating artware, which comprises the following steps: electrostatically adsorbing iron powder on the surface of a silica gel mold, and then uniformly spraying a curing agent to obtain a pre-pouring mold; uniformly mixing unsaturated polyester resin, stone powder and color paste according to a mass ratio of 1: (0.7-0.9): (0.004-0.005) to obtain a primary mixture; uniformly mixing and stirring the primary mixture, reduced iron powder, cyclohexanone peroxide and cobalt iso-octoate according to the mass ratio of 1: (1.2-1.6): (0.02-0.03): (0.005-0.01) to obtain a castable; pouring the castable into a pre-pouring mold, and carrying out curing molding and demolding to obtain a blank body; and the blank is subjected to alkali washing, air drying, polishing, saline oxidation treatment, rust wiping and transparent paint spraying for finishing, and a finished product is obtained. The method has the advantages of diversified molded bodies and good corrosion-resistant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of imitation cast iron material processing, and more specifically, to a process for producing an imitation cast iron corrosion rust effect handicraft. Background Art

[0002] Conventional cast iron corrosion effect products require the use of sand casting molds. The workpieces are made of iron ore and iron powder that are melted in a high-temperature furnace and cast. The casting industry is a highly polluting and energy-intensive process, and the casting process is greatly limited in its shape due to the influence of the process and mold.

[0003] Crafts imitating cast iron corrosion rust effect can use resin as the main material and iron powder as the auxiliary material. The crafts imitating cast iron corrosion effect can not only greatly save energy consumption and suppress production pollution, but also use soft silicone molds with strong plasticity and quick-drying resin slurry to diversify the shapes and make the crafts more vivid and realistic.

[0004] Therefore, how to prepare a new imitation cast iron handicraft that has the advantages of diversified shaping and good corrosion resistance is a problem to be solved. Summary of the invention

[0005] In order to prepare a new imitation cast iron handicraft with the advantages of diversified shaping and good corrosion resistance, the present application provides a production process of an imitation cast iron corrosion rust effect handicraft.

[0006] The present application provides a production process for a craftwork imitating cast iron corrosion rust effect, which adopts the following technical solution: A production process of a craftwork imitating cast iron corrosion rust effect, comprising the following steps: S1. Electrostatically adsorb iron powder on the surface of the silicone mold, and then evenly spray the curing agent to obtain a pre-casting mold; the mass ratio of iron powder to curing agent is 1:0.2-0.5; S2, unsaturated polyester resin, stone powder, color paste in a mass ratio of 1:0.7-0.9:0.004-0.005 mixed uniformly to obtain a primary mixture; the mass ratio of iron powder to unsaturated polyester resin is 1:1.5-2; S3, the primary mixed material is mixed and stirred evenly with reduced iron powder, cyclohexanone peroxide and cobalt isooctanoate in a mass ratio of 1:1.2-1.6:0.02-0.03:0.005-0.01 to obtain a casting material; S4, pouring the casting material into the precasting mold, curing and molding, and demoulding to obtain an embryo body; S5, the embryo body is alkali washed, air-dried, and polished until iron powder appears to obtain a semi-finished product; S6. The semi-finished product is treated with salt water oxidation, and then the rust is wiped off and sprayed with transparent paint to obtain a finished handicraft.

[0007] By adopting the above technical scheme, the electrostatic adsorption effect of the silicone mold and the iron powder is utilized to facilitate the iron powder to be uniformly adsorbed on the surface of the silicone mold, and then the curing agent is attached to the surface of the silicone mold; after the unsaturated polyester resin is mixed with the stone powder and the color paste, the cross-linking and curing effect of the curing agent attached to the surface of the silicone mold and the unsaturated polyester resin in the initial mixture is utilized to facilitate the iron powder electrostatically adsorbed on the silicone mold to stably adhere to the surface of the embryo, thereby achieving an imitation cast iron effect; and the addition of stone powder further enhances the strength of the embryo, and cooperates with the dispersed filling effect of the reduced iron powder in the embryo, further improving the strength of the embryo, thereby achieving an imitation cast iron effect; after the surface iron powder is oxidized to remove the rust, the surface will not be easily oxidized again, thereby having a better anti-corrosion effect.

[0008] The flow effect of unsaturated polyester resin in the liquid castable makes the castable evenly dispersed at any position in the silicone mold. Even some complex silicone mold edges, pits, micro-gaps and other positions can penetrate the castable, thereby achieving the dispersion of iron powder at special locations, facilitating the preparation of complex imitation cast iron crafts and giving them the advantage of diversified shaping.

[0009] Preferably, the electrostatic adsorption of iron powder in S1 specifically comprises the following steps: First, flaky iron powder is evenly sprayed on the surface of the silicone mold, and then polyethylene glycol solution is evenly sprayed on the gaps and pits of the mold. The mass ratio of flaky iron powder to polyethylene glycol solution is 1:0.1-0.2, and the polyethylene glycol solution is composed of polyethylene glycol ethanol solution and spherical iron powder in a mass ratio of 1:0.2-0.5.

[0010] By adopting the above technical scheme, flaky iron powder is sprayed onto the surface of the silicone mold. The larger specific surface area of ​​the flaky iron powder is used to facilitate large-area contact with the silicone mold, thereby facilitating the electrostatic adsorption of the flaky iron powder in the silicone mold. For some gaps and pits in the mold, it is not easy for the flaky iron powder to penetrate and fill. The penetration effect of the polyethylene glycol ethanol solution is used to carry the spherical iron powder for filling, thereby realizing the preparation of handicrafts with complex shapes, and the handicrafts can present the advantages of diverse shaping shapes.

[0011] The polyethylene glycol ethanol solution not only has a good flow effect, but also facilitates the adhesion of spherical iron powder to the surface of the silicone mold. When demolding, it is also convenient for special shapes to be demolded well, and it is not easy to affect the overall effect of the handicraft. At the same time, the hydroxyl groups in the polyethylene glycol are easy to cross-link and bond with the unsaturated polyester resin and the curing agent, thereby promoting the stable adhesion of spherical iron powder and flaky iron powder to the surface of the embryo, ensuring the imitation cast iron effect on the surface of the handicraft, and at the same time making the handicrafts with complex shapes have a better molding effect.

[0012] Preferably, the average particle size of the flaky iron powder is 40-80 meshes, and the average particle size of the spherical iron powder is 300-500 meshes.

[0013] By adopting the above technical scheme, the particle sizes of flaky iron powder and spherical iron powder are limited, ensuring that the flaky iron powder has a larger specific surface area, which is convenient for contact with the silicone mold to ensure the electrostatic adsorption effect, and the spherical iron powder is convenient for rolling and filling into pits, gaps and other positions, and pits and gaps are avoided as much as possible. Finally, during the grinding process, it is necessary to grind to the position where the iron powder appears, which is easy to affect the shape of the handicraft defined by the silicone mold, and the uniform adhesion of the iron powder can maximize the effect of preparing complex handicrafts.

[0014] Preferably, the curing agent is cyclohexanone peroxide.

[0015] By adopting the above technical scheme, the reaction of free radicals in cyclohexanone peroxide with unsaturated double bonds in unsaturated polyester resin will trigger a polymerization chain reaction. As the polymerization reaction proceeds, the polyester resin gradually changes from liquid to solid to form a hard solidified material. In this process, free radicals continuously combine with double bonds in the resin to form new free radicals, and continue to react with other double bonds. This chain reaction will lead to the continuous growth of the polyester resin molecular chain and eventually form a cross-linked network structure, thereby ensuring the strength and quality stability of handicrafts. Combined with the filling effect of stone powder and reduced iron powder, the strength and stability of handicrafts are further ensured.

[0016] Preferably, the silicone mold is a pretreated silicone mold, and the pretreated silicone mold is prepared by the following method: mixing sodium hydroxymethylglycine solution and needle-shaped iron powder at a mass ratio of 1:0.1-0.2 and stirring them evenly to obtain a composite material; placing the mold in the composite liquid for shaking treatment, then taking out the mold, washing the mold with water, and drying it to obtain a pretreated silicone mold.

[0017] By adopting the above technical scheme, the sodium hydroxymethylglycinate solution has good fluidity, which is convenient for the needle-shaped iron powder to enter the tip of the micro-gap, the tip of the tip and the top of the gap. The penetration of the needle-shaped iron powder ensures that the complex structure of the complex handicraft can be well formed, and it is not easy to cause poor precision of the handicraft due to the final wear; and the sodium hydroxymethylglycinate has amino groups and other groups, which are convenient for cross-linking with polyethylene glycol, thereby improving the stability of handicraft molding.

[0018] Preferably, the stone powder is prepared from heavy calcium carbonate, polyethyleneimine solution and hydroxyapatite whiskers in a mass ratio of 1:0.1-0.2:0.05-0.1.

[0019] By adopting the above technical scheme, heavy calcium carbonate, polyethyleneimine solution and hydroxyapatite whiskers are matched, and the viscosity of the polyethyleneimine solution is utilized to facilitate the adhesion of hydroxyapatite whiskers to the surface of heavy calcium carbonate. The filling of heavy calcium carbonate is combined with the cross-linking effect of amino groups in polyethyleneimine and unsaturated polyester resin, and the connecting effect of the larger specific surface area of ​​hydroxyapatite whiskers is utilized to improve the dispersion and cross-linking effect of stone powder in unsaturated polyester resin, thereby further ensuring the strength and stability of handicrafts.

[0020] Preferably, the color paste consists of red paste and black paste in a mass ratio of 2.5-3:1.

[0021] By adopting the above technical solution, uniform color adjustment is performed, thereby ensuring the preparation effect of handicrafts.

[0022] Preferably, the average particle size of the reduced iron powder is 50-80 mesh.

[0023] By adopting the above technical solution, the dispersion and filling effect of the reduced iron powder is guaranteed, so that the handicraft has the advantages of better corrosion resistance and diversified shaping.

[0024] Preferably, the specific steps of alkali washing are as follows: Mix sodium hydroxide and water evenly to obtain alkaline solution, completely immerse the embryo in the alkaline solution, adjust the pH to 13, and completely immerse for 18-22 minutes. Take out the embryo, brush it, and rinse it with water.

[0025] By adopting the above technical solution, the surface grease is removed, thereby ensuring the cleanliness of the embryo, making it easier to oxidize the semi-finished product, and after wiping off the rust, the corrosion resistance of the finished product can be guaranteed.

[0026] Preferably, the specific steps of the salt water oxidation treatment are as follows: Mix industrial salt and water in a ratio of 1:9-11 to obtain brine. Spray the brine evenly on the surface of the semi-finished product once every three hours. After sealing for 3-6 days, take out the product workpiece.

[0027] By adopting the above technical solution, after the semi-finished product is oxidized, the rust is removed and then a transparent paint is sprayed to finish it, so that the finished workpiece has better corrosion resistance. In summary, this application has the following beneficial effects: 1. The electrostatic adsorption effect between the silicone mold and the iron powder is used to facilitate the iron powder to be evenly adsorbed on the surface of the silicone mold, and then the curing agent is attached to the surface of the silicone mold; after the unsaturated polyester resin is mixed with the stone powder and the color paste, the curing agent attached to the surface of the silicone mold and the cross-linking curing effect of the unsaturated polyester resin in the initial mixture are used to facilitate the iron powder electrostatically adsorbed on the silicone mold to stably adhere to the surface of the embryo to achieve the imitation cast iron effect; after the surface iron powder is oxidized and the rust is removed, the surface will not be easily oxidized again, thus having a better anti-corrosion effect.

[0028] 2. The flow effect of unsaturated polyester resin in liquid casting material makes the casting material evenly dispersed at any position in the silicone mold. Even some complex silicone mold edges, pits, micro-gaps and other positions can penetrate the casting material. The pits of the silicone mold correspond to the vertices of the handicraft, thereby realizing the dispersion of iron powder at special locations, facilitating the preparation of complex imitation cast iron handicrafts and making them present the advantages of diversified shaping. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] The following raw materials are all commercially available.

[0031] Preparation example of pre-treated silicone mold Preparation Example 1: The pretreated silicone mold is prepared by the following method: 0.2 kg of needle-shaped iron powder is added to 1 kg of sodium hydroxymethylglycinate solution and the mixture is stirred evenly, wherein the sodium hydroxymethylglycinate solution is a sodium hydroxymethylglycinate aqueous solution with a mass fraction of 1%, and the average length of the needle-shaped iron powder is 20 μm, to obtain a composite material; the mold is placed in the composite liquid for vibration treatment, the mold is completely immersed in the composite liquid, and the mixture is shaken for 10 minutes, and then the mold is taken out, the inside of the mold is washed with water twice, and after drying, a pretreated silicone mold is obtained.

[0032] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: Add 0.1 kg of needle-shaped iron powder to 1 kg of sodium hydroxymethylglycine solution, mix and stir evenly to obtain a composite material; place the mold in the composite liquid for shaking treatment, the mold is completely immersed in the composite liquid, shaken for 10 minutes, and then the mold is taken out, the inside of the mold is washed with water twice, and after drying, a pretreated silicone mold is obtained.

[0033] Preparation example of stone powder Preparation Example 3: Stone powder is prepared by the following method: 0.2 kg of polyethyleneimine solution is evenly sprayed on the surface of 1 kg of heavy calcium carbonate, and then 0.1 kg of hydroxyapatite whiskers are added, mixed evenly, dried, and dispersed until the heavy calcium carbonate does not stick to each other and agglomerate to obtain a finished product; the heavy calcium carbonate is passed through an 80-mesh sieve, the polyethyleneimine solution is a polyethyleneimine aqueous solution with a mass fraction of 1%, and the average length of the hydroxyapatite whiskers is 100 μm.

[0034] Preparation Example 4: This preparation example differs from Preparation Example 3 in that: 0.1 kg of polyethyleneimine solution is evenly sprayed on the surface of 1 kg of heavy calcium carbonate, and then 0.05 kg of hydroxyapatite whiskers are added, mixed evenly, and dried and dispersed until the heavy calcium carbonate does not stick to each other and agglomerate to obtain a finished product. Example

[0035] Embodiment 1: A production process of a craftwork imitating cast iron corrosion rust effect: S1. Spray flaky iron powder evenly on the surface of the silicone mold, the silicone mold is the pretreated silicone mold prepared in Preparation Example 1; then spray polyethylene glycol solution evenly on the gaps and pits on the pretreated silicone mold, spray 2g of polyethylene glycol solution per square centimeter, the mass ratio of flaky iron powder to polyethylene glycol solution is 1:0.1, the average particle size of the flaky iron powder passes through a 60-mesh sieve, the polyethylene glycol solution is composed of a polyethylene glycol ethanol solution and spherical iron powder in a mass ratio of 1:0.4, the mass fraction of the polyethylene glycol ethanol solution is 10%, the polyethylene glycol is polyethylene glycol 1000, the average particle size of the spherical iron powder passes through a 400-mesh sieve, and the spherical iron powder and the flaky iron powder are iron powder in total; then evenly spray a curing agent, the curing agent is cyclohexanone peroxide, to obtain a precast mold; the mass ratio of iron powder to curing agent is 1:0.4; S2, unsaturated polyester resin and stone powder, color paste are mixed uniformly in a mass ratio of 1:0.8:0.004, the stone powder is selected from the stone powder prepared in Preparation Example 3, the color paste is composed of red paste and black paste in a mass ratio of 2.5:1, and a primary mixture is obtained; the mass ratio of iron powder to unsaturated polyester resin is 1:1.8; S3, the primary mixed material is mixed and stirred evenly with reduced iron powder, cyclohexanone peroxide and cobalt isooctanoate in a mass ratio of 1:1.5:0.025:0.005 to obtain a casting material; the reduced iron powder is sieved through a 60-mesh sieve; S4, pour the casting material into the precast mold, seal the grouting port with a cover plate, roll the mold to allow the slurry to flow evenly in every part of the mold, and demould after the slurry in the mold is completely solidified to obtain an embryo body; S5. After the embryo is removed from the mold, it is washed with alkali. Sodium hydroxide and water are mixed and stirred evenly to obtain an alkali solution. The embryo is completely immersed in the alkali solution, and the pH is adjusted to 13. The embryo is completely immersed for 20 minutes. The embryo is taken out, brushed and rinsed with water, and then air-dried. After air-drying, it is polished with 300-mesh sandpaper to remove the surface resin of the embryo. The surface resin is polished until iron powder is seen to obtain a semi-finished product. S6. Place the semi-finished product in an airtight space, mix industrial salt and water at a ratio of 1:10 to obtain brine, spray the brine evenly on the surface of the semi-finished product, spray once every three hours, take out the product workpiece after sealing for 5 days, wipe off the rust, spray transparent lacquer for finishing, and after the transparent lacquer is cured, form a paint layer with an average thickness of 0.1μm to obtain the finished handicraft.

[0036] Embodiment 2: This embodiment differs from Embodiment 1 in that: S1. Spray flaky iron powder evenly on the surface of the silicone mold, the silicone mold is the pretreated silicone mold prepared in Preparation Example 2; then spray polyethylene glycol solution evenly on the tip, gap and pit position of the pretreated silicone mold, spray 2g of polyethylene glycol solution per square centimeter, the mass ratio of flaky iron powder to polyethylene glycol solution is 1:0.1, the average particle size of the flaky iron powder passes through a 40-mesh sieve, the polyethylene glycol solution is composed of a polyethylene glycol ethanol solution and spherical iron powder in a mass ratio of 1:0.2, the mass fraction of the polyethylene glycol ethanol solution is 10%, the polyethylene glycol is polyethylene glycol 1000, the average particle size of the spherical iron powder passes through a 300-mesh sieve, and the spherical iron powder and the flaky iron powder are iron powder in total; then evenly spray a curing agent, the curing agent is cyclohexanone peroxide, to obtain a precast mold; the mass ratio of iron powder to curing agent is 1:0.2; S2, unsaturated polyester resin and stone powder, color paste are mixed uniformly in a mass ratio of 1:0.7:0.004, the stone powder is selected from the stone powder prepared in Preparation Example 4, and the color paste is composed of red paste and black paste in a mass ratio of 3:1 to obtain a primary mixture; the mass ratio of iron powder to unsaturated polyester resin is 1:1.5; S3, the primary mixed material is mixed and stirred evenly with reduced iron powder, cyclohexanone peroxide and cobalt isooctanoate in a mass ratio of 1:1.2:0.02:0.005 to obtain a casting material; the reduced iron powder is sieved through a 50-mesh sieve; S4, pour the casting material into the precast mold, seal the grouting port with a cover plate, roll the mold to allow the slurry to flow evenly in every part of the mold, and demould after the slurry in the mold is completely solidified to obtain an embryo body; S5. After the embryo is removed from the mold, it is washed with alkali. Sodium hydroxide and water are mixed and stirred evenly to obtain an alkali solution. The embryo is completely immersed in the alkali solution, and the pH is adjusted to 13. The embryo is completely immersed for 18 minutes. The embryo is taken out, brushed and rinsed with water, and then air-dried. After air-drying, it is polished with 300-mesh sandpaper to remove the resin on the surface of the embryo. The semi-finished product is obtained by polishing until iron powder is seen. S6. Place the semi-finished product in an airtight space, mix industrial salt and water in a ratio of 1:9 to obtain brine, spray the brine evenly on the surface of the semi-finished product, spray once every three hours, take out the product workpiece after sealing for 3 days, wipe off the rust, spray transparent lacquer for finishing, and after the transparent lacquer is cured, form a paint layer with an average thickness of 0.1μm to obtain the finished handicraft.

[0037] Embodiment 3: This embodiment differs from Embodiment 1 in that: S1. Spray flaky iron powder evenly on the surface of the silicone mold, the silicone mold is the pretreated silicone mold prepared in Preparation Example 1; then spray polyethylene glycol solution evenly on the tip, gap and pit position of the pretreated silicone mold, spray 2g of polyethylene glycol solution per square centimeter, the mass ratio of flaky iron powder to polyethylene glycol solution is 1:0.2, the average particle size of the flaky iron powder passes through an 80-mesh sieve, the polyethylene glycol solution is composed of a polyethylene glycol ethanol solution and spherical iron powder in a mass ratio of 1:0.5, the mass fraction of the polyethylene glycol ethanol solution is 10%, the polyethylene glycol is polyethylene glycol 1000, the average particle size of the spherical iron powder passes through a 500-mesh sieve, and the spherical iron powder and the flaky iron powder are iron powder in total; then evenly spray a curing agent, the curing agent is cyclohexanone peroxide, to obtain a precast mold; the mass ratio of iron powder to curing agent is 1:0.5; S2, unsaturated polyester resin, stone powder, color paste are mixed uniformly in a mass ratio of 1:0.9:0.005, the stone powder is selected from the stone powder prepared in Preparation Example 3, the color paste is composed of red paste and black paste in a mass ratio of 3:1, and a primary mixture is obtained; the mass ratio of iron powder to unsaturated polyester resin is 1:2; S3, the primary mixed material is mixed and stirred evenly with reduced iron powder, cyclohexanone peroxide and cobalt isooctanoate in a mass ratio of 1:1.6:0.03:0.01 to obtain a casting material; the reduced iron powder is sieved through an 80-mesh sieve; S4, pour the casting material into the precast mold, seal the grouting port with a cover plate, roll the mold to allow the slurry to flow evenly in every part of the mold, and demould after the slurry in the mold is completely solidified to obtain an embryo body; S5. After the embryo is removed from the mold, it is washed with alkali. Sodium hydroxide and water are mixed and stirred evenly to obtain alkali solution. The embryo is completely immersed in the alkali solution, and the pH is adjusted to 13. The embryo is completely immersed for 22 minutes. The embryo is taken out, brushed and rinsed with water, and then air-dried. After air-drying, it is polished with 300-mesh sandpaper to remove the surface resin of the embryo. The semi-finished product is obtained by polishing until iron powder is seen. S6. Place the semi-finished product in an airtight space, mix industrial salt and water in a ratio of 1:11 to obtain brine, spray the brine evenly on the surface of the semi-finished product, spray once every three hours, take out the product workpiece after sealing for 6 days, wipe off the rust, spray transparent lacquer for finishing, and after the transparent lacquer is cured, form a paint layer with an average thickness of 0.1μm to obtain the finished handicraft.

[0038] Embodiment 4: This embodiment differs from Embodiment 1 in that: In S1, the flake iron powder is replaced by spherical iron powder of the same mass.

[0039] Embodiment 5: This embodiment differs from Embodiment 1 in that: No polyethylene glycol solution was added to S1.

[0040] Embodiment 6: This embodiment differs from Embodiment 1 in that: No spherical iron powder was added to the polyethylene glycol solution of S1.

[0041] Embodiment 7: This embodiment differs from Embodiment 1 in that: The silicone mold in S1 is not treated with the sodium carboxymethylglycinate solution and the needle-shaped iron powder, that is, it is an ordinary silicone mold.

[0042] Embodiment 8: This embodiment differs from Embodiment 1 in that: No polyethyleneimine solution and hydroxyapatite whiskers were added to the stone powder of S2.

[0043] Comparative Example Comparative Example 1: The difference between this comparative example and Example 1 is that: No curing agent was added to S1.

[0044] Comparative Example 2: The difference between this comparative example and Example 1 is that: No stone powder was added to S2.

[0045] Performance testing 1. Corrosion resistance test The handicrafts prepared by the methods of Examples 1-7 and Comparative Example 1 were respectively subjected to salt spray corrosion for 120 hours with reference to GB / T10125-2021, and the corrosion area per unit area was recorded, and the data was recorded.

[0046] 2. Body shape diversity test The handicrafts were prepared by the methods of Examples 1-3 and 5-7, respectively, wherein the silicone mold had 10 pits, the average diameter of the bottom of the pits was 0.1 mm, and there were 5 wedge-shaped structures, the average width of the deepest part of the wedge was 0.5 mm, and the deepest part of the wedge was similar to a gap. After the handicraft was prepared and formed, the difference between the average diameter of the bottom of the pits in the silicone mold and the average diameter of the bottom of the corresponding pits on the handicraft was recorded, and the difference between the average width of the deepest part of the gap on the silicone mold and the average width of the deepest part of the corresponding gap on the handicraft was recorded. The average values ​​of all differences of the handicrafts prepared by the methods of Examples 1-3 and 5-7 were calculated respectively, and recorded as the average difference. The larger the average difference, the poor imitation cast iron effect at the complex position of the handicraft, and the high amount of surface erasure, thereby affecting the shape and size accuracy of the finished handicraft.

[0047] 3. Strength test The handicrafts prepared by the methods of Examples 1-3, 5, 8 and Comparative Example 2 were tested for compressive strength using a universal press and the data were recorded.

[0048] Table 1 Performance test table (“ / ” in the table means that the corresponding embodiment or comparative example did not test the item, so there is no data) project <![CDATA[Corrosion area / mm 2 / cm 2 > Average difference / mm Compressive strength / MPa Example 1 0 0 24.5 Example 2 0.5 0.04 23.6 Example 3 0 0 24.8 Example 4 2.2 / / Example 5 1.0 0.1 22.7 Example 6 0.8 0.07 / Example 7 0.4 0.03 / Example 8 / / 21.4 Comparative Example 1 5.6 / / Comparative Example 2 / / 19.8 It can be seen from Examples 1-3 and Table 1 that the prepared handicrafts have good corrosion resistance, and the complex handicrafts have high precision, and are not prone to the problem of no iron powder covering the edges and protruding positions. At the same time, the compressive strength is high, indicating that the effect of imitating cast iron has been achieved.

[0049] Combining Example 1 and Examples 4-8 and Table 1, it can be seen that Example 4 replaces the flake iron powder with spherical iron powder of equal mass. Compared with Example 1, the corrosion area of ​​the handicraft prepared in Example 4 is larger than that in Example 1; this indicates that the flake iron powder can be adsorbed on the surface of the silicone mold over a larger area, thereby facilitating uniform loading of the flake iron powder on the surface of the handicraft, while the contact area between the spherical iron powder and the silicone mold is smaller than the contact area between the flake iron powder and the silicone mold, which easily affects the adhesion effect of the iron powder on the surface of the handicraft, thereby affecting the corrosion resistance of the handicraft.

[0050] No polyethylene glycol solution was added to Example 5, and no spherical iron powder was added to the polyethylene glycol solution in Example 6. Compared with Example 1, the corrosion areas of the handicrafts prepared in Examples 5 and 6 were larger than those in Example 1, the average difference was greater than that in Example 1, and the compressive strength of Example 5 was lower than that of Example 1. This indicates that the polyethylene glycol ethanol solution combined with the spherical iron powder can be further filled in the embryo prepared by the unsaturated polyester resin, thereby improving the strength of the handicraft, and the uniform dispersion of the spherical iron powder can further promote the uniform loading of the iron powder on the surface of the handicraft, thereby ensuring the corrosion resistance and processing accuracy of the handicraft.

[0051] The silicone mold of Example 7 was not treated with sodium carboxymethylglycinate solution and needle-shaped iron powder, and was an ordinary silicone mold. Compared with Example 1, the corrosion area of ​​the handicraft prepared in Example 7 was larger than that in Example 1, and the average difference was larger than that in Example 1; this indicated that the sodium carboxymethylglycinate solution could not only increase the amino groups on the surface of the silicone mold, making it easier for iron powder and unsaturated polyester resin to adhere to the surface of the silicone mold, but also make the raised positions and edge positions on the handicraft evenly loaded with iron, thereby ensuring the accuracy and quality of the preparation of the loaded imitation cast iron handicraft.

[0052] In Example 8, no polyethyleneimine solution and hydroxyapatite whiskers were added to the stone powder. Compared with Example 1, the compressive strength of the handicraft prepared in Example 8 was lower than that in Example 1, indicating that the addition of polyethyleneimine solution and hydroxyapatite whiskers can improve the strength of the handicraft.

[0053] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that no curing agent is added to Comparative Example 1. Compared with Example 1, the corrosion area of ​​the handicraft prepared in Comparative Example 1 is larger than that in Example 1; this indicates that the addition of the curing agent can promote the adhesion of iron powder to the surface of the embryo, thereby achieving uniform loading of iron powder on the surface of the handicraft, and the prepared handicraft has a better anti-corrosion effect.

[0054] Comparative Example 2 did not add stone powder. Compared with Example 1, the compressive strength of the handicraft prepared in Comparative Example 2 was lower than that in Example 1, indicating that the addition of stone powder increased the strength of the handicraft and achieved the effect of imitating cast iron.

[0055] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A process for producing a craftwork imitating cast iron corrosion rust effect, characterized in that: The following steps are included: S1. Electrostatically adsorb iron powder on the surface of the silicone mold, and then evenly spray the curing agent to obtain a pre-casting mold; the mass ratio of iron powder to curing agent is 1:0.2-0.5; S2, unsaturated polyester resin, stone powder, color paste in a mass ratio of 1:0.7-0.9:0.004-0.005 mixed uniformly to obtain a primary mixture; the mass ratio of iron powder to unsaturated polyester resin is 1:1.5-2; S3, the primary mixed material is mixed and stirred evenly with reduced iron powder, cyclohexanone peroxide and cobalt isooctanoate in a mass ratio of 1:1.2-1.6:0.02-0.03:0.005-0.01 to obtain a casting material; S4, pouring the casting material into the precasting mold, curing and molding, and demoulding to obtain an embryo body; S5, the embryo body is alkali washed, air-dried, and polished until iron powder appears to obtain a semi-finished product; S6. The semi-finished product is treated with salt water oxidation, and then the rust is wiped off and sprayed with transparent paint to obtain a finished handicraft.

2. The process for making a craftwork imitating cast iron corrosion rust effect according to claim 1, characterized in that: The electrostatic adsorption of iron powder in S1 specifically includes the following steps: First, flaky iron powder is evenly sprayed on the surface of the silicone mold, and then polyethylene glycol solution is evenly sprayed on the gaps and pits of the mold. The mass ratio of flaky iron powder to polyethylene glycol solution is 1:0.1-0.2, and the polyethylene glycol solution is composed of polyethylene glycol ethanol solution and spherical iron powder in a mass ratio of 1:0.2-0.

5.

3. The manufacturing process of a craftwork imitating cast iron corrosion rust effect according to claim 2, characterized in that: The average particle size of the flaky iron powder is 40-80 meshes, and the average particle size of the spherical iron powder is 300-500 meshes.

4. The process for making a craftwork imitating cast iron corrosion rust effect according to claim 1, characterized in that: The curing agent is cyclohexanone peroxide.

5. The process for making a craftwork imitating cast iron corrosion rust effect according to claim 1, characterized in that: The silicone mold is a pretreated silicone mold, and the pretreated silicone mold is prepared by the following method: mixing and stirring a sodium hydroxymethylglycine solution and needle-shaped iron powder at a mass ratio of 1:0.1-0.2 to obtain a composite material; placing the mold in the composite liquid for shaking treatment, then taking out the mold, washing the mold with water, and drying it to obtain a pretreated silicone mold.

6. The process for making a craftwork imitating cast iron corrosion rust effect according to claim 1, characterized in that: The stone powder is prepared from heavy calcium carbonate, polyethyleneimine solution and hydroxyapatite whisker in a mass ratio of 1:0.1-0.2:0.05-0.

1.

7. The manufacturing process of a craftwork imitating cast iron corrosion rust effect according to claim 1, characterized in that: The color paste is composed of red paste and black paste in a mass ratio of 2.5-3:

1.

8. The process for making a craftwork imitating cast iron corrosion rust effect according to claim 1, characterized in that: The average particle size of the reduced iron powder is 50-80 meshes.

9. The process for making a craftwork imitating cast iron corrosion rust effect according to claim 1, characterized in that: The specific steps of alkali washing are as follows: Mix sodium hydroxide and water evenly to obtain alkaline solution, completely immerse the embryo in the alkaline solution, adjust the pH to 13, and completely immerse for 18-22 minutes. Take out the embryo, brush it, and rinse it with water.

10. The process for making a craftwork imitating cast iron corrosion rust effect according to claim 1, characterized in that: The specific steps of the salt water oxidation treatment are as follows: Mix industrial salt and water in a ratio of 1:9-11 to obtain brine. Spray the brine evenly on the surface of the semi-finished product once every three hours. After sealing for 3-6 days, take out the product workpiece.